2016
DOI: 10.1021/acsami.6b04644
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Ethoxy-Functional Polysiloxane Wrapped LiNi0.6Co0.2Mn0.2O2 Cathode with Improved Cycling Performance for Rechargeable Li-Ion Battery

Abstract: Dealing with the water molecule on the surface of LiNi0.6Co0.2Mn0.2O2 (NCM) cathode and hydrogen fluoride in the electrolyte is one of the most difficult challenges in Li-ion battery research. In this paper, the surface polymerization of tetraethyl orthosilicate (TEOS) on NCM to generate ethoxy-functional polysiloxane (EPS) wrapped NCM (E-NCM) cathode under mild conditions and without any additions is utilized to solve this intractable problem. The differential scanning calorimetry, transmission electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 58 publications
3
57
0
Order By: Relevance
“…A large number of secondary particles cracked and even pulverized (Figure a‐b), which confirms the structure of pristine was visibly destroyed on account of the dissolution of TMs . Furthermore, large cracks and pulverization of particles lead more fresh active sites to interact with electrolyte, generating more TMs dissolution . However, the surface morphology and structure of 100‐NiF 2 cathode are well preserved (Figure c–d ) , which means that NiF 2 can protect the cathode from corroding of electrolyte.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…A large number of secondary particles cracked and even pulverized (Figure a‐b), which confirms the structure of pristine was visibly destroyed on account of the dissolution of TMs . Furthermore, large cracks and pulverization of particles lead more fresh active sites to interact with electrolyte, generating more TMs dissolution . However, the surface morphology and structure of 100‐NiF 2 cathode are well preserved (Figure c–d ) , which means that NiF 2 can protect the cathode from corroding of electrolyte.…”
Section: Resultsmentioning
confidence: 71%
“…[37,38] Furthermore, large cracks and pulverization of particles lead more fresh active sites to interact with electrolyte, generating more TMs dissolution. [5,39] However, the surface morphology and structure of 100-NiF 2 cathode are well preserved (Figure 6c-d), which means that NiF 2 can protect the cathode from corroding of electrolyte. On the one hand, the suppression of TMs dissolution reduces the loss of active cathode materials, [40] restraining the capacity attenuation.…”
Section: Characterizationmentioning
confidence: 98%
See 1 more Smart Citation
“…[8,9] In reality, different synthesis conditions, such as different atmospheres, have significant effects on surface, structure, and performance of NRLC, which is still not satisfactory. [10][11][12][13] Until now, many measures are taken to improve the performance of NRLC such as metal ions doping and surface coating. Doping of sodium improves the rate capability and the capacity retention of LiNi 0.8 Co 0.15 Al 0.05 by suppressing the hexagonal to hexagonal (H2/H3) phase transition to alleviate the particle pulverization.…”
Section: Introductionmentioning
confidence: 99%
“…Through time-resolved X-ray diffraction & mass spectrometry (TR-XRD/MS), Bak et al [39] revealed the same phase transformation upon heating the charged electrode. Taken together, the deterioration of chemical and structural stability of cathode material will be accelerated, leading to continuous capacity decay and thus inferior electrochemical performances [40,41]. , and olivine compounds with three-dimensional pathways (i.e., LiFePO4).…”
Section: Hypothesis/problem Statementmentioning
confidence: 99%